Thermoelastic analysis of dislocation generation during edge-defined film-fed growth of polygonal shells - Wu, C. H.; Lambropoulos, J. C.
A thermoelastic model is used to predict qualitatively the dislocation generation for the edge-defined film-fed growth (EFG)of polygonal shells. The eight-node degenerate shell element with drilling degree of freedom and Eringen's micropolar elasticity theory are used to compute the stresses of the polygonal shell under arbitrary temperature decay. Based on the calculated stresses in the polygonal shell, the evolution of dislocations and creep strain rates are calculated by the Alexander-Haasen constitutive law. The effect of the geometrical shape of the shell is also discussed.
Keywords: CALCULATIONS; CREEP; DENSITY (SPECIFIC GRAVITY); DISLOCATIONS (CRYSTALS); GEOMETRY; MATHEMATICAL MODELS; STRAIN RATE; STRESSES; TEMPERATURE DISTRIBUTION